Nineteenth through early 20th Century Female and Male Statures within the Household - Scott A. Carson (Center for Economic Studies and Ifo Institute (CESifo), 2020)
When other measures for material conditions are scarce or unreliable, the use of height is now common to evaluate economic conditions during economic development. However, throughout US economic development, height data by gender have been slow to emerge. Throughout the late 19th and early 20th centuries, female and male statures remained constant. Agricultural workers had taller statures than workers in other occupations, and the female agricultural height premium was over twice that of males. For both females and males, individuals with fairer complexions were taller than their darker complexioned counterparts. Gender collectively had the greatest explanatory effect associated with stature, followed by age and nativity. Socioeconomic status and birth period had the smallest collective effects with stature.
Keywords: C10; C40; D10; I10; N30; 330; gender studies; stature by gender; economic transitions